Inexplicable COVID-19! Would pathological autopsy be the panacea? - Parekh, Utsav; Kanchan, Tanuj; Krishan, Kewal (Acta Biomedica Atenei Parmensis, 2021)
SARS-CoV-2 has swamped the entire world, unfolding into a COVID-19 pandemic. Efforts are on to develop an understanding of the various aspects related to SARS-CoV-2 and COVID-19. A pathological autopsy can play a vital role in understanding the pathophysiology of the disease, which may be vital in evolving effective management strategies. Despite its significance in the present circumstances, only a limited number of pathological autopsies are being conducted worldwide. The paper stresses on the need for taking up pathological autopsies globally and discusses its present status and the way forward, along with international perspectives and recommendations for consideration of pathological autopsy.